2013
DOI: 10.1080/00222895.2013.798251
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Affects the Vertical Curvature in Human Grasping Movements

Abstract: When humans make grasping movements their digits' paths are curved vertically. In a previous study the authors found that this curvature is largely caused by the local constraints at the start and end of the movement. Here the authors examined the contribution of gravity to the part of the curvature that was not explained by the local constraints. Subjects had to grasp a tealight (small cylinder) while sitting on a chair. The authors could rotate the whole setup, including the subject, relative to gravity, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…To test this prediction, we ran a control experiment in which participants tilted backwards by 20°o r 60°were asked to hit a static target in synchrony with the last of a predictable series of stationary audio-visual stimuli. We found that body posture affected significantly arm kinematics, consistent with previous studies on the effects of gravity on arm movements (Papaxanthis et al 1998, Pinter et al 2012Gentili et al 2007;Verheij et al 2013;Gaveau et al 2016), although it did not affect interception timing even after extensive practice.…”
Section: The Hypothesis and The Findingssupporting
confidence: 91%
See 3 more Smart Citations
“…To test this prediction, we ran a control experiment in which participants tilted backwards by 20°o r 60°were asked to hit a static target in synchrony with the last of a predictable series of stationary audio-visual stimuli. We found that body posture affected significantly arm kinematics, consistent with previous studies on the effects of gravity on arm movements (Papaxanthis et al 1998, Pinter et al 2012Gentili et al 2007;Verheij et al 2013;Gaveau et al 2016), although it did not affect interception timing even after extensive practice.…”
Section: The Hypothesis and The Findingssupporting
confidence: 91%
“…; Verheij et al . ; Gaveau et al . ), although it did not affect interception timing even after extensive practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing corpus of research indicating that humans use their knowledge of earth gravity in a broad range of tasks, such as grasping (Verheij, Brenner, & Smeets, 2013), catching and interception (Bosco, Delle Monache, & Lacquaniti, 2012;Jörges, Hagenfeld, & López-Moliner, 2018;Lacquaniti et al, 2013;McIntyre, Zago, & Berthoz, 2001;McIntyre, Zago, Berthoz, & Lacquaniti, 2003;Senot, Zago, Lacquaniti, & McIntyre, 2005;Senot et al, 2012;Zago et al, 2004;Zago, McIntyre, Senot, & Lacquaniti, 2009;, duration estimation (Moscatelli & Lacquaniti, 2011) or the perception of biological motion (Jokisch & Troje, 2003;Maffei et al, 2015;Simion, Regolin, & Bulf, 2008), while arbitrary accelerations are generally neglected (Benguigui & Bennett, 2010;Benguigui, Ripoll, & Broderick, 2003) or used insufficiently. Here we examined ocular pursuit and spatial estimation in a linear prediction motion task that emphasized extrapolation of occluded accelerative object motion.…”
Section: Introductionmentioning
confidence: 99%